2006
DOI: 10.1037/0012-1649.42.2.283
|View full text |Cite
|
Sign up to set email alerts
|

Does Barbie make girls want to be thin? The effect of experimental exposure to images of dolls on the body image of 5- to 8-year-old girls.

Abstract: The ubiquitous Barbie doll was examined in the present study as a possible cause for young girls' body dissatisfaction. A total of 162 girls, from age 5 to age 8, were exposed to images of either Barbie dolls, Emme dolls (U.S. size 16), or no dolls (baseline control) and then completed assessments of body image. Girls exposed to Barbie reported lower body esteem and greater desire for a thinner body shape than girls in the other exposure conditions. However, this immediate negative impact of Barbie doll was no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
150
5
8

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(169 citation statements)
references
References 37 publications
6
150
5
8
Order By: Relevance
“…Dittmar, Halliwell and Ive (2006) revealed in their study concerning Barbie dolls' effect that this identification with dolls started at a very early age with child's gaining independence. They stated that these over identification would also effect these children's physical images in the future.…”
Section: Resultsmentioning
confidence: 99%
“…Dittmar, Halliwell and Ive (2006) revealed in their study concerning Barbie dolls' effect that this identification with dolls started at a very early age with child's gaining independence. They stated that these over identification would also effect these children's physical images in the future.…”
Section: Resultsmentioning
confidence: 99%
“…[45][46][47][48][49] The inadequate adjustment in sexual attitudes revealed by the overweight adolescent girls in our study could be a result of dissatisfaction with their bodies, resulting in feelings of unattractiveness in comparison with the cultural 'standards' imposed by Western society. 11,12,21,22,25 Adolescent girls are reported to be preoccupied with their body weight and body image. 11,12,14,16,25 They strive to achieve socially imposed 'ideal' body proportions, valuing themselves only in relation to their appearance.…”
Section: Discussionmentioning
confidence: 99%
“…Research has shown that adolescent girls are becoming increasingly preoccupied by their body image and burdened with the beauty ideal imposed by the media and society. [11][12][13]21,22 Body dissatisfaction in adolescent girls may imply development of negative self-perception and self-evaluation, which can result in development of adolescent depression and eating disorders. 12,13,[22][23][24] The need to accept a body image that is changing radically from that of childhood is actualised in the adolescent period.…”
mentioning
confidence: 99%
“…To verify that this manipulation was successful we also assessed a motivational consequence of thin-ideal exposure: desire for thinness. Previous studies indicate that thin-ideal exposure increases women's desire for thinness (Dittmar, Halliwell, & Ive, 2006;Dittmar, Halliwell, & Stirling, 2009). Thus, we expected women in the thin-ideal condition, compared to the control condition, to report greater desire for a thinner body shape.…”
Section: The Present Studymentioning
confidence: 99%